How Should a Teacher Be According to The Teacher’s Views? - Ömer Cem Karacaoğlu (Research Synergy Foundation, 2024)
Identifying and enhancing teacher competencies and qualifications is crucial for advancing the quality of education. This qualitative study aimed to explore teachers' qualifications and self-perceptions through interviews with 78 teachers across various disciplines. The objective was to understand discrepancies between teachers' self-views and critical perceptions of colleagues, thereby identifying essential competencies. Semi-structured interviews, employing a qualitative approach, facilitated a thorough exploration of teacher perspectives. The study group included classroom, English, Turkish, math, science, philosophy, religious culture, computer, biology, history, chemistry, physical education, music, Turkish language, literature, painting, and physics teachers. Open-ended questions elicited opinions on colleague qualifications, essential teacher competencies, and self-perceptions. The findings revealed that experienced teachers demonstrated higher confidence, while beginners expressed a commitment to improvement. Communication skills, empathy, love for students, subject knowledge, self-development, patience, tolerance, and passion for teaching were highlighted as crucial competencies. Teachers emphasized the need for a balance between personal and professional qualities, advocating for pedagogical formation, contemporary teaching approaches, and technology proficiency. The study concludes that continuous professional development is vital, emphasizing the importance of both human-oriented qualities and technical competencies for effective teaching. This research provides a foundation for raising teachers' awareness of competence assessment and development, urging educational institutions to support ongoing teacher growth.